Collisional depolarization of OH(A) studied by Zeeman quantum beat spectroscopy - Brouard, M; Bryant, A; Burak, I; Marinakis, S; Quadrini, F; Garcia, I; Vallance, C (2005)
The depolarization of the rotational angular momentum of electronically excited OH(2Sigma;) radicals through collisions with water molecules has been measured using Zeeman quantum beat spectroscopy. The new data have permitted the evaluation of OH(A) state-specific quenching and angular momentum depolarization cross-sections for superthermal OH(A) radicals with mean relative velocities centred around 3500 m s-1. The quenching cross-sections are compared both with values available in the literature, and with predictions based on a simple harpoon model, and are found to be in good qualitative accord with previous findings. For the lowest rotational levels studied, the depolarization cross-sections (which include contributions from both elastic and inelastic processes in OH(A)) are found to approach ∼100 Å2, only slightly below the high-temperature cross-sections for rotational energy transfer determined elsewhere. The data suggest that under the present conditions rotational energy transfer is accompanied by significant depolarization. The cross-section for the translational moderation of superthermal OH(X) by water is also determined in the present study. © 2005 Taylor and Francis Group Ltd.